Envisioning the Experience of Others: Moral Imagination, Practical Wisdom and the Scope of Empathy - Fletcher, Natalie M. (Philosophical Inquiry in Education, 2016)
The concept of empathy has gained appeal in many educational initiatives in recent years, notably in the charitable sector, yet conceptual confusions endure and the challenges associated with educating for empathy tend not to receive the attention they deserve. This article strives to help clarify the concept of empathy for educative purposes by examining one such challenge—conceived as "narrow empathetic scope"—drawing on central ideas from neo-Aristotelian virtue theory. The article explores the ways in which moral imagination, as a precursor to empathy, may be uniquely able to assist with the cultivation of practical wisdom in children since it enables them to visualize contexts they have not yet encountered and broaden the moral lens through which they approach and assess their lived experience. The article will also present the Philosophy for Children model as an effective pedagogical method for cultivating the virtue of empathy through morally imaginative dialogue.